PREPARATORY WORK FOR COMPARISON OF EFFECT OF WINTER STAY ON DIFFERENT FOOD TYPES AND WINTER STAY INFLUENCE ON BEE-COLONIES DEVELOPMENT - Сенчук, Т. Ю. (Scientific Progress & Innovations, 2013)
Nowadays vast amount of farmland on which bees can gather winter feed is occupied by sunflower. Sunflower honey has high crystallization ability that highly worsens bee wintering and can cause bee colonies death. Object of our researches is to determine the influence of honey with low crystallization ability and sunflower honey on wintering and bee colonies’ development in early spring. We have done necessary preparatory work for organization of wintering on various kinds of honey. We have determined honey reserve of the territory, have made honey balance of the territory and calendar of meliferous plant blossoming and provided bee colonies with different feed stocks for winter.